2016
DOI: 10.5294/laclil.2016.9.2.4
|View full text |Cite
|
Sign up to set email alerts
|

Is EMI Enough? Perceptions from University Professors and Students

Abstract: Internationalization of higher education aims to develop foreign language and intercultural and international competences (IIC). To achieve this, universities worldwide have implemented strategies such as teaching content subjects in English, also known as English mediated instruction (EMI). However, there is scant research on the positive and negative aspects related to EMI implementation in Latin America. For this reason, this case study explores the perceptions of a group of computer science professors, stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
39
0
5

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(46 citation statements)
references
References 33 publications
2
39
0
5
Order By: Relevance
“…However, the studies that considered other stakeholders' views in addition to those of EMI instructors and students, i.e. programme heads and office staff (Hou, Morse, Chiang, & Chen, 2013), administrative personnel (Doiz, Lasagabaster, & Sierra, 2014), program administrators (Corrales, Paba Rey, & Santiago Escamilla, 2016), and university leaders at different levels (Duong & Chua, 2016) were maintained as part of our dataset. The two authors of the paper reviewed each publication and when any disagreement relating to the interpretation of the publications' content occurred, the issue was discussed until consensus was achieved.…”
Section: The Impact Of Online Technologies and English Medium Instrucmentioning
confidence: 99%
“…However, the studies that considered other stakeholders' views in addition to those of EMI instructors and students, i.e. programme heads and office staff (Hou, Morse, Chiang, & Chen, 2013), administrative personnel (Doiz, Lasagabaster, & Sierra, 2014), program administrators (Corrales, Paba Rey, & Santiago Escamilla, 2016), and university leaders at different levels (Duong & Chua, 2016) were maintained as part of our dataset. The two authors of the paper reviewed each publication and when any disagreement relating to the interpretation of the publications' content occurred, the issue was discussed until consensus was achieved.…”
Section: The Impact Of Online Technologies and English Medium Instrucmentioning
confidence: 99%
“…Otros trabajos en América Latina (McDougald, 2015;Corrales, Paba y Santiago, 2016) muestran que es limitada la implementación del enfoque EMI/CLIL en educación superior.…”
Section: Referente Teóricounclassified
“…It is important to consider, however, that students in the fields of social sciences tend to have greater English language proficiency than those of engineering or sciences (Wächter & Maiworm, 2014 Little research on the topic has been carried out in Africa or Latin America, so it is difficult to say how it is being implemented in those regions. Though EMI is growing in Latin America, the only Latin American study found at the time of this writing is from Colombia (Corrales, Paba-Rey, & Escamilla-Santiago, 2016). Both Dearden's (2014) (Airey, 2015;Ball & Lindsay, 2013), the effects of EMI on academic performance (Airey, 2011;Dafouz & Camacho-Miñano, 2016), proficiency by disciplinary area (Dimova & Kling 2018), the use of L1 (Ibrahim, 2001;Macaro, 2019;Pun & Macaro, 2019), motivation (Doiz & Lasagabaster, 2018), compensatory strategies (Kling, 2016), required competencies of instructors (Macaro, Akincioglu, & Han, 2019) and of learners (Sancho-Guinda & Thompson, Aizawa, Curle, & Rose, 2019), and instructor identity (Dafouz, 2018;Kling, 2015), among others.…”
Section: English As a Medium Of Instructionmentioning
confidence: 99%